PENEGAKAN HUKUM TERHADAP PROSES HUKUM PEMBUKTIAN TERBALIK TERBATAS DALAM PERKARA PIDANA KORUPSI - Kuntong, Dalmasius (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT The legal process of reversing evidence is limited in the case of corruption preceded by a defense conducted by the defendant in which the defendant attempted to prove that he did not commit a criminal act of corruption. Regarding the effectiveness of reversed evidence can not be explained with certainty. This is because in general the juridical rule that this applies to everyone who is entangled or becomes a defendant is given a chance to prove. According to research usually in terms of proof, the defendant can say that the wealth he has obtained from inheritance and grants. So in this case the relationship between the prosecutor and the defendant in the proof. However, the provisions that the defendant admits wrongly before the trial, that what he has done is fully acknowledged, with clear explanations of criminal incidents committed and all in accordance with the testimony of the victim's witnesses and other evidence, perfect. In its implementation to reveal the case of corruption is the obstacle to obtain supporting evidence. Proving the element of corruption, it should not be said that corruption is detrimental to the state's finances. In the case investigation, the obstacle faced is usually at the time of proof, because in this case it is very risky and complicated and to say the certainty in this case needs expert witnesses who are expected to help. So although there is a corruption case can not necessarily direct investigators say that there is a state loss, but the investigator must carefully handle and overcome it. In case of reversal of the existing constraints, among others, the investigator to find the defendant's criminal offense and to propose the offense finds difficulties if it turns out the process is incorrect. The inverse proof is the right of the suspect to defend himself against the allegations imposed by evidence. Administratively the existing constraints are in the handling of notification letter to the local government, where in this case for the regional level must be known by the governor, and for the central level must be known by the president. In addition to the above it is incriminating to obtain preliminary evidence in conducting an investigation. Keywords  :  Corruption, Limited Proof of Best